A reliable unicast routing protocol for mobile ad hoc network - Sargolzaey, Hadi (2013)
Mobile Ad Hoc Network (MANET) is a special and attractive type of new wireless networks. It is an autonomous system that can dynamically be set up anywhere and anytime without using any pre-existing network infrastructure and its mobile hosts are free to move randomly. Host mobility in MANETs causes failure of wireless links between nodes and breaks all the routes that use these links. Consequently, route reconstructions are needed, which is one of the most crucial issues for this type of wireless networks. There are two common solutions to this problem which increase the route reliability (lifetime) in MANETs; increasing the reliability of the links by using more reliable links and multipath route discovery. In this thesis, both these schemes are used to develop a reliable unicast routing protocol for MANETs. As the first step, an efficient cross layer link reliability metric is proposed for reliable link selection. Simulation results show that by using this link reliability metric in route discovery, route reliability is increased with higher efficiency in comparison to other link reliability metrics. Next a reliable position based clustering routing protocol is designed. In this protocol the mobile nodes form disjoint sets of clusters, and for increasing the stability of these clusters, the aforementioned cross layer link reliability metric is used for cluster formation. A route is constructed and represented by a sequence of clusters and more reliable links are selected for data transfer inside and between the clusters. Because of the multiple links which usually exist between the clusters, multipath route scheme is used in this routing protocol in addition to the reliable link selection. Simulation results show that by using this protocol the lowest number of route reconstructions is achieved in comparison with the other related protocols and we have 79% to 86% reductions in ute reconstruction number in different network conditions. It is also shown that the algorithm contributed greatly to reducing control overhead and although we have extra control packets overhead due to the cluster formation and maintenance, we see 27% to 38% control packets overhead reduction in different network conditions.